Livelihood Diversification Strategies of Khmer and Kinh Farmers in the Mekong Delta since the 1993 Land Law (Global Journal of Human-Social Science, 2014)
Abstract not found
Keywords: land law; market mechanism; commodity; livelihood; diversification strategies